A 1995 Social Accounting Matrix (SAM) for Zambia - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
This dataset is a 1995 social accounting matrix (SAM) for Zambia. Data sources include national accounts data, government budgets, balance of payments statistics, trade data, household surveys, and farm budgets. This SAM comprises 28 activities, 27 commodities, 6 factors of production (4 labor categories, 1 capital, and 1 land account), 4 household types, and one account each for enterprises, government, rest-of-the-world, and investment/savings. For a description of the construction and use of this dataset, download the Trade and Macroeconomics Division Discussion Paper Number 49: (PDF 1.4MB)